2014
DOI: 10.2478/s11536-013-0269-z
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarein ameliorates tongue cancer cells via mitochondria

Abstract: AbstractTo investigate the mechanism in Scutellarein-induced apoptosis of SAS human tongue cancer cells, inhibitory effects of Scutellarein on SAS cells were detected by MTT assay. Cell apoptosis was analyzed by flow cytometry. Ultrastructural changes of SAS cells were observed by transmission electron microscopy (TEM). Mitochondrial transmembrane potential (ΔΨm) were analyzed by JC-1 [5,5,6,6-Tetrachloro-1,1,3,3-tetraethylbenzimidazolylcarbocyanine iodide]. Western blotting wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Recent studies have showed that baicalein and scutellarein can induce apoptosis of cancer cells. 23,24) The mechanism of apoptosis induced by baicalein and scutellarein has been widely reported. Baicalein and scutellarein effectively up-regulated the expression of mitochondrial Bax and caspase-3, down-regulated the expression of Bcl-2, and decreased the mitochondrial transmembrane potential (ΔΨm).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have showed that baicalein and scutellarein can induce apoptosis of cancer cells. 23,24) The mechanism of apoptosis induced by baicalein and scutellarein has been widely reported. Baicalein and scutellarein effectively up-regulated the expression of mitochondrial Bax and caspase-3, down-regulated the expression of Bcl-2, and decreased the mitochondrial transmembrane potential (ΔΨm).…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein and scutellarein effectively up-regulated the expression of mitochondrial Bax and caspase-3, down-regulated the expression of Bcl-2, and decreased the mitochondrial transmembrane potential (ΔΨm). [23][24][25] These data suggest that the mechanism by which baicalein and scutellarein induce apoptosis involves the mitochondrial signaling pathway. It has been reported that luteolin, apigenin and chrysin in addition to inducing apoptosis through the ubiquitin-proteasome pathway, also can induce apoptosis through the mitochondrial signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] Several studies have proposed that the anticancer mechanism of scutellarein involves a reactive oxygen species (ROS)-mediated mitochondriadependent pathway. [11,13,14] However, whether scutellarein has an effect in OC has not been thoroughly evaluated.…”
Section: Introductionmentioning
confidence: 99%